Electrometric studies on uranyl molybdates as a function of pH - Prasad, Shiva; Barros, Jaqueline Viana (Eclética Química, 1998)
The formation and composition of uranyl molybdates obtained by the interaction of uranyl acetate and sodium molybdate at specific pH levels 7.6, 5.5 and 4.1 have been studied by employing electrometric techniques involving pH and conductometric titrations. The results provide cogent evidence for the formation of three uranyl molybdates having the molecular formulae UO2O.MoO3, 3UO2O.7MoO3 and 2UO2O.8MoO3 in the vicinity of pH 5.7, 4.6 and 3.8, respectively. Analytical investigations of the compounds have also been carried out which substantiate the results of electrometric study.